MoS2 field-effect transistor with graphene contacts. Issue 32 (7th August 2017) - Andleeb, Shaista; Eom, Jonghwa; Rauf Naz, Nabila; Singh, Arun Kumar
Abstract : We report a simple methodology to improve the performance of graphene contacted bi-layer MoS2 field-effect transistors by combination of nitrogen gas and deep-ultraviolet light treatment. Abstract : Tailoring the electronic properties of molybdenum disulfide (MoS2 ) is essential to obtain the best performance of its electronic and optoelectronic devices. Here, we report a simple methodology to improve the performance of bi-layer (BL) MoS2 field-effect transistors (FETs) by a combination of nitrogen (N2 ) gas and deep-ultraviolet (DUV) light treatment. Threshold voltages of BL MoS2 FETs shifted towards a negative gate voltage after treatment with N2 gas in the presence of DUV light. The charge-carrier mobility of BL MoS2 was improved significantly after exposure to N2 gas under DUV light irradiation. The carrier density of BL MoS2 was enhanced after treatment with N2 gas in the presence of DUV light. We believe that our work may also help improve the performance of other two-dimensional nanomaterials.